Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengunjung Pada Hotel Kyriad Sadurengas Kabupaten Paser - Clara Natalia Sagala, Feronika; Althalets, Fareis (Jurnal Etnik: Ekonomi-Teknik, 2022)
Service quality is part of the marketing stimulus, the existence of which affects consumer psychology. If the quality of service, price and facilities are perceived positively, it means that consumers are satisfied which has an impact on repeat purchases made by consumers. The purpose of this study was to examine the quality of service on visitor satisfaction at the Kyriad Sadurengas Hotel, Paser Regency. The population in this study were guests of the Kyriad Sadurengas Hotel, Kabuoaten Paser, totaling 100 respondents. The variables used in this study consisted of the independent variable, namely the Service Quality variable (X), and the dependent variable, namely Visitor Satisfaction (Y). The results of the analysis using simple regression analysis. The data collection technique is based on the source, including primary data through observation, interviews, questionnaires or questionnaires, and includes documentation. Secondary data, among others, by searching for literature in the form of previous research journals, and text books that have to do with the variables to be studied. The data analysis technique used Validity Test and Reliability Test. As for the data analysis technique method using the Determination Analysis method (R2), hypothesis testing using the T test. The results show that the Service Quality variable (X) simultaneously has a significant effect on Customer Satisfaction (Y) Kyriad Sadurengas Hotel, Paser Regency.